Diversity and Metabolic Potentials of Subsurface Crustal Microorganisms from the Western Flank of the Mid-Atlantic Ridge - Zhang, Xinxu; Feng, Xiaoyuan; Wang, Fengping (Frontiers in Microbiology, 2016)
Deep-sea oceanic crust constitutes the largest region of the earth’s surface. Accumulating evidence suggests that unique microbial communities are supported by iron cycling processes, particularly in the young (<10 million-year old), cool (<25°C) subsurface oceanic crust. To test this hypothesis, we investigated the microbial abundance, diversity, and metabolic potentials in the sediment-buried crust from “North Pond” on western flank of the Mid-Atlantic Ridge. Three lithologic units along basement Hole U1383C were found, which typically hosted ∼104 cells cm-3 of basaltic rock, with higher cell densities occurring between 115 and 145 m below seafloor. Similar bacterial community structures, which are dominated by Gammaproteobacterial and Sphingobacterial species closely related to iron oxidizers, were detected regardless of variations in sampling depth. The metabolic potentials of the crust microbiota were assayed by metagenomic analysis of two basalt enrichments which showed similar bacterial structure with the original sample. Genes coding for energy metabolism involved in hydrocarbon degradation, dissimilatory nitrate reduction to ammonium, denitrification and hydrogen oxidation were identified. Compared with other marine environments, the metagenomes from the basalt-hosted environments were enriched in pathways for Fe3+ uptake, siderophore synthesis and uptake, and Fe transport, suggesting that iron metabolism is an important energy production and conservation mechanism in this system. Overall, we provide evidence that the North Pond crustal biosphere is dominated by unique bacterial groups with the potential for iron-related biogeochemical cycles.